A discursive constructionist approach to narrative in language teaching and learning research. (November 2021) - Prior, Matthew T.; Talmy, Steven
Abstract: This article describes a discursive constructionist (DC) approach to narrative in second/foreign language teaching and learning research. We begin by sketching an historical and theoretical background of constructionism. Next, we describe how DC advances contemporary narrative research by prioritizing analysis of narrative construction, that is, the in situ mobilization of the constructed and constructive elements of discourse that story-tellers use to build narrative worlds. Drawing on an analysis of two narrative episodes from focus group research with ESL teachers, we examine the construction and versioning of narrative worlds, identities, and knowledge. We also consider an additional affordance that attends a DC approach to narrative research—methodography—which opens up for analysis the situated work of the researcher/data analyst. We conclude with suggestions for future applications of DC.